Single-centre experience of emergency hernia surgery during COVID-19 pandemic: a comparative study of the operative activity and outcomes before and after the outbreak - Adnan Malik; Mohamed Zohdy; Aftab Ahmad; Charalampos Seretis (Medicinski glasnik, 2021)
Aim: The outbreak of COVID-19 pandemic in January 2020 affected largely the elective operating for non-urgent surgical pathologies, such as hernias, due to periodical cancellations of the operating lists on a worldwide scale. To the best of our knowledge, the long-term impact of the COVID-19 pandemic in relation to the emergency hernia surgery operative workload and postoperative outcomes remains largely unknown. Methods: Retrospective research of admission, operation and inpatient records of all patients who underwent emergency surgery over a 2-year period (2019-2020) was done. Results: An 18% increase in terms of emergency hernia surgery operating volume, with a 23% increase of visceral resections due to unsalvageable herniated content strangulation was found. Overall morbidity did not increase during the pandemic period and there was no postoperative mortality or occurrence of COVID-19 related complications. Conclusion: Emergency operative management of acutely symptomatic hernias can be safely performed even during the COVID-19 infection peak waves; hernia taxis should be reserved only for patients unfit or unwilling to undergo upfront surgery
Keywords: abdominal hernia; coronavirus; SARS; general surgery